The triumphal cross of the cathedral of Nevers: painting technique and examination - Nadia Bertoni Cren; Stéphane Cren (Medievalista)
The large polychrome wooden cross preserved in the Saint-Cyr et Sainte-Julitte cathedral in Nevers was badly damaged during the bombing in July 1944. Restored and put on display on a modern cross in front of the choir, the sculpture suffered a new fall in 2015. The conservation of the work, directed by DRAC-CRMH of Burgundy-Franche-Comté, was preceded by a phase of technical study. Micro-stratigraphic, taxonomic and radiometric analyses and the dendrochronology of the cross were carried out. The dendrochronology of the cross of Nevers and the comparison with radiocarbon dating place the elaboration of the work in the last quarter of the 12th century while confirming the contemporaneousness of the cross with the sculpture. The quality of the triumphal cross of Nevers is highlighted even more by this dating which testifies to the richness of the formal contributions in Burgundy in the 12th century.